Analisis Penerapan Model Tujuan Rasional Dalam Meningkatkan Efektivitas Implementasi E-Government Sebagai Realisasi Aksiologi Dalam Administrasi Pemerintahan Daerah - Hasan Al Bana; Nurhaliza Putri; Tasya Dwi Melani; Ditha Linggar Parawansa; Alma Wulan Astriasty Lomban Wullur (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Policies and regulations in improving the effectiveness of E-Government implementation are important steps for local governments to realize axiology in local governance. This is because policies and regulations can be a guideline in the development and implementation of E-Government services that are effective, efficient, and follow the needs of the community. In this research, the local government will be faced with a problem in which there is an implementation related to the implementation of E-Government. Starting from the strategy to the development of the implementation of the E-Government implementation. The effectiveness of E-Government implementation in Local Government will be considered good if the time, cost, resources, and level of public satisfaction are following the rational goal model and reflect axiological values in administration.